Biochar, an eco-friendly approach for the treatment of wastewater (Nepal Journal of Environmental Science, 2024)
The agroindustry by-products viz., peanut shell, bagasse, corn cob, sawdust, rice and wheat straw, pressmud, etc. are produced in immense quantity which are directly burnt or disposed to the landfills. These agroindustry by-products can be used to make various value-added products. The agroindustry by-product can be used to prepare biochar, and such agroindustry by-product-based biochar can be used for the treatment of wastewater. As wastewater contains pathogens, total dissolved and volatile solids, the treatment of wastewater is very essential, and biochar can be the solution to it. The biochar can be prepared by pyrolysis at a high temperature (700 oC) in a limited supply of oxygen. This use of biochar for the treatment of wastewater is eco-friendly and economical and can be used for various purposes.